Dampak Smartphone Terhadap Kepribadian Anak Dan Pembelajaran Al-Qur’an - Saputra, Adha; Salfage, Dandi; Muhamad Ragil Gilang Qadrullah; Mahfud Ihsanuddin; Alghifari; Laode Muhammad Khatami (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2023)
This service aims to explore the various kinds of impacts and changes that arise in children's personalities and Qur'anic learning This service method uses field methods. Based on the results of the service, the use of smartphones is very risky to cause various impacts on children's personalities and their Qur'anic learning. Among them are the impact of games, social media, and non-scientific content that can cause addiction and attitude changes in the child's own personality. These changes are also very visible in their Qur'anic learning, this happens because of the loss of focus and willingness of a child to learn the Qur'an when they are exposed to addiction to smartphone devices. However, with proper use and supervision, the use of smartphones can also be a useful tool and medium in the educational and spiritual development of children.